Rapid Prototyping in Orthopaedic Surgery: A User's Guide - Mark Frame; James S. Huntley (The Scientific World Journal)
Rapid prototyping (RP) is applicable to orthopaedic problems involving three dimensions, particularly fractures, deformities, and reconstruction. In the past, RP has been hampered by cost and difficulties accessing the appropriate expertise. Here we outline the history of rapid prototyping and furthermore a process using open-source software to produce a high fidelity physical model from CT data. This greatly mitigates the expense associated with the technique, allowing surgeons to produce precise models for preoperative planning and procedure rehearsal. We describe the method with an illustrative case.